2018
DOI: 10.1259/bjr.20180126
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and agreement of stiffness measurements using gradient-echo and spin-echo MR elastography sequences in unselected patients undergoing liver MRI

Abstract: In clinical setting, there is a high correlation between the GRE and SE MRE stiffness measurements, independently of the degree of liver fat infiltration measured by PDFF. A strong correlation between SE-MRE sequences is found even in patients with iron overload.  Advances in knowledge: Our study addresses liver iron and fat content simultaneously to describing the technical feasibility and correlation between different MRE sequences in consecutive unselected patients refereed for liver MRI. EPI SE-MRE should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 37 publications
0
38
1
Order By: Relevance
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, 31 studies fulfilled the eligibility criteria for our analysis, including eight studies using both GRE and SE‐EPI sequences, 22 studies using only a GRE sequence, , , , , , , , and one study using only an SE‐EPI sequence . As one study using both GRE and SE‐EPI sequences potentially overlapped with a population in another GRE sequence outcome study, we did not include the outcomes of this study in the evaluation of the pooled proportion of technical failure of GRE sequences, but used it only for the head‐to‐head comparison between GRE and SE‐EPI sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic characteristics of the included studies are shown in Table . In brief, subjects were enrolled prospectively in 16 studies and retrospectively in 15 studies , , , , , , , . The mean patient ages in 14 studies , , , , , , , , ranged from 25 to 60.5 years, but we could not analyze patient age in the other studies, because they did not report demographic information on all subjects, but reported only those with successful examinations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations